Protective effect of cytosine-phosphate-guanosine oligodeoxynucleotide against experimental mastitis induced by Cryptococcus neoformans infection in goats: Nidhal R. Mahdi1, Shaimaa N. Yassein2 and Jenan M. Khalaf3 - Mahdi, Nidhal R. (The Iraqi Journal of Veterinary Medicine, 2017)
The present study investigated the effect of synthetic non-methylated oligonucleotides containing Cytosine-phosphate-guanosine dinucleotides (Cytosine-phosphate-guanosine oligodeoxynucleotide) on caprine mastitis with Heat Killed Cryptococcus neoformans Ag. 20 healthy local breed does were used with weight ranging of 25-30 Kg and free of mastitis by examination via California Mastitis Test and Somatic Cell Count. The does were allotted into four equal groups, the first group (G1) was treated intramammary with 100μg/kg of Cytosine-phosphate-guanosine oligodeoxy nucleotide on fifth day postpartum in the right mammary gland while the left mammary gland served as control and were infused with sterile phosphate buffered saline. On day 8 postpartum repeat dosages of Cytosine-phosphate-guanosine oligodeoxynucleotide and phosphate buffered saline were infused respectively. On day 9 pp the right mammary gland was infused with 2ml of 2x108 cell/ml of Heat Killed Cryptococcus neoformans Ag. The second group (G2) was infused at day 9 postpartum with 2ml of 2x108 cell/ml of Heat Killed Cryptococcus neoformans Ag in the right mammary gland only. The third group (G3) was left until the challenge test done after one week of immunization in the G1 and G2, by inoculation of 2ml of 5x106 viable C. neoformans in the right mammary gland. The fourth group (G4) was kept as a control receiving 2ml of sterile PBS. Blood samples were collected at 0, 5, 10, 20, 30 and 40 days of the study, to determine the antibody titer by passive haemagglutination assay, while the cell mediated immunity was evaluated by detecting the goat Interferon Gamma by ELISA test and Phagocytic index. Also the cell mediated immunity was determined by delayed type hypersensitivity test after 21 days of immunization. The results showed a significant variation (P≤0.05) between vaccinated groups (G1 and G2) and the control. However, there was a significant increase (P≤0.05) of skin thickness shown after 48 hrs in the G1compared to G2. High level of Interferon Gamma concentration was noticed in the G1 as compared with other groups. Moreover, cell mediated immunity developed effectively in the G1 which was noted by a significant increase (P≤0.05) of phagocytic activity of polymorphonuclear cells. The high level of antibody titer was observed in the G1 as compared with other groups. In conclusion: These results suggest that vaccination with Cytosine-phosphate-guanosine oligodeoxynucleotide plus Heat Killed Cryptococcus neoformans Ag intramammary lead to a good protection of caprine mammary glands against C. neoformans mastitis.